Effect of Integrated Nitrogen Management and Intercropping Systems on Yield Attributes and Yield of Maize - JAT, P.C.; RATHORE, S.S.; SHARMA, R.K. (Indian Journal of Hill Farming, 2015)
The field experiments were conducted to study the effect of integrated nitrogen management (INM) and intercropping systems on yield attributes and yield of maize during kharif seasons of year 2009 and 2010 at KVK, Chomu, Jaipur (Rajasthan). The treatments included cropping patterns viz. sole maize, maize + one row mung bean, maize + two row mung bean and sole mung bean and integrated nitrogen management i.e. control, 60 kg N/ha, 60 kg N/ha + biofertilizer (Rhizobium + Azospirillium + PSB), 120 kg N/ha, 120 kg N/ha + bio-fertilizer (Rhizobium + Azospirillium + PSB) and biofertilizer (Rhizobium + Azospirillium + PSB). Intercropping maize and mung bean markedly influenced cobs/plant, length of cobs, grains/cob, 1000-grains weight, grain yield/ha and stover yield/ha of maize. Higher stover and grain yield was found with maize + two rows of mung bean over maize + one row of mung bean and sole maize in both the years. The INM also significantly affected yield attributes and yield of maize in both the years of experimentation. Application of 120 kg N/ha + biofertilizers (Rhizobium + Azospirillium + PSB), produced maximum number of cobs/plant, number of grains/cob, cob length, 1000-grains weight, grain and stover yield of maize in both the years.